La doctrine mystique de Denys l'Aréopagite - Bernard, Charles André (Gregorianum, 1987)
The article proposes to determine the principal traits of the mystical doctrine of Dionysius the Areopagite. From the methodological point of view, the accent is put upon the necessity to situate this doctrine in the whole of Dionysian thought keeping in mind its liturgical spirit: in this sense, the importance of the apophatic dimension normally identified with the mysticism of Dionysius is equated with the sense of praise which refers to the positive aspects of theology. Besides, it is necessary to consider the mystical aspect itself. While previous research strove above all to define the essential act, ecstasy, it appears more correct to take into account the complexity of spiritual activity: it includes a symbolisation as well as a speculative aspect. Even presupposing these, for Dionysius it is necessary to go beyond the perceptible as well as the intellectual operations. While recognising Dionysius' great merit of having brillantly clarified the mystical problem, one could not expect him to have developed all its implications. His speculative effort at least opened up decisive formulae which have traversed the centuries and have influenced all Christian mysticism.